Combining Oncolytic Adenovirus with Radiation—A Paradigm for the Future of Radiosensitization - O’Cathail, Sean M.; Pokrovska, Tzveta D.; Maughan, Timothy S.; Fisher, Kerry D.; Seymour, Leonard W.; Hawkins, Maria A. (Frontiers in Oncology, 2017)
Oncolytic viruses and radiotherapy represent two diverse areas of cancer therapy, utilising quite different treatment modalities and with non-overlapping cytotoxicity profile. It is therefore an intriguing possibiltiy to consider that oncolytic ('cancer-killing') viruses may act as cancer-selective radiosensitisers, enhancing the therapeutic consequences of radiation treatment on tumours whilst exerting minimal effects on normal tissue. There is a solid mechanistic basis for this potential synergy, with many viruses having developed strategies to inhibit cellular DNA repair pathways in order to protect themselves, during genome replication, from unwanted interference by cell processes that are normally triggered by DNA damage. Exploiting these abilities to inhibit cellular DNA repair following damage by therapeutic irradiation may well augment the anticancer potency of the approach. In this review we focus on oncolytic adenovirus, the most widely developed and best understood oncolytic virus, and explore its various mechanisms for modulating cellular DNA repair pathways. The most obvious effects of the various adenovirus serotypes are to interfere with activity of the MRN complex, temporally one of the first sensors of double stranded DNA damage, and inhibition of DNA ligase IV, a central repair enzyme for healing double stranded breaks by non-homologous end-joining (NHEJ). There have been several preclinical and clinical studies of this approach and we assess the current state of progress. In addition, oncolytic viruses provide the option to promote a localised proinflammatory response, both by mediating immunogenic death of cancer cells by oncosis and also by encoding and expressing proinflammatory biologics within the tumour microenvironment. Both of these approaches provide exciting potential to augment the known immunological consequences of radiotherapy, aiming to develop systems capable of creating a systemic anticancer immune response following localised tumour treatment.